PERMODELAN UJI LOGAM BERAT PADA BADAN AIR, BIOTA DAN SEDIMEN DI PERAIRAN MUARA DAS BARITO - Dini Sofarini; Abdur Rahman; Ichsan Ridwan (Bumi Lestari Journal of Environment, 2012)
This research aimed to determine heavy metal content at water body, sediment and biota, determining plankton what overflows and parameter of water quality which not fulfill standard criterion quality of water in Estuary of Barito River. Method of data Analyse used to determine status of water quality with STORET model and EQI (Environmental Quality Index) Model, and calculation of indices for the analysis of plankton and Geographic Information System. Result of research show heavy metal rate at body of water especially Hg (0.2753 mg/l), dan Pb (0.17667 mg/l) and residing at biota (Giant Prawn have accumulate by heavy metal of Hg. Pb, Cu, As, Cr6+ and Cd. Sediment residing at Estuary of Barito River have accumulate by heavy metal but still under maximum boundary which have been specified. Result of research show calculation by using method of ordinary kriging with semivariogram/covariance modeling for heavy metal model at body obtained value of Average of standard error equal to 0.00609 (RMS = 0.00512) at Estuary River of Kelayan), 0.02441 (RMS = 0.02638) at Estuary of Alalak and 0.01641 (RMS = 0.01430) at station of Estuary River of Kuin. Result of calculation Semivariogram of heavy metal model at sediment, obtained of Average of Standard Error equal to 0.98181 (RMS = 1.14015) at station I, station II equal to 1.14015 (RMS = 1.79179) and station III equal to 1.19635 (RMS = 1.25590). Status of water quality at station perception according to Model of STORET categorized is weight, while pursuant to Model of Environmental Quality Index (EQI) categorized as impure territorial water.